2018
DOI: 10.1038/s41598-018-28896-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the tolerance to room temperature and viability of freeze-dried mice spermatozoa over long-term storage at room temperature under vacuum

Abstract: Freeze-drying has been frequently used to preserve food and microorganisms at room temperature (RT) for extended periods of time; however, its application to mammalian species is difficult. Here, we developed a method to prolong the stability of freeze-dried (FD) mice spermatozoa at RT for more than one year without using any cryoprotectant agents. Our data showed that maintaining a vacuum in ampoules is critical to ensuring the viability of FD spermatozoa, as the stability of spermatozoa DNA increased when im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…However, recent advances in reproductive biotechnology allow us to resurrect mammalian species from ‘dead’ cell nuclei. For example, healthy offspring were obtained not only from frozen cadavers 79 , but also from FD mouse spermatozoa that had been preserved at RT for more than 1 year 14,15 or even exposed to space radiation by preservation at the International Space Station for 9 months 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent advances in reproductive biotechnology allow us to resurrect mammalian species from ‘dead’ cell nuclei. For example, healthy offspring were obtained not only from frozen cadavers 79 , but also from FD mouse spermatozoa that had been preserved at RT for more than 1 year 14,15 or even exposed to space radiation by preservation at the International Space Station for 9 months 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, previously, we and others have demonstrated that the dead bodies or frozen cadavers of mammalian species could be ‘revived’ when their spermatozoa or somatic cell nuclei were transplanted into oocytes to produce fertilized or cloned offspring 710 . In addition, recently, we and others have demonstrated that the complete drying of mammalian spermatozoa—similar to the anhydrobiotic state of Tardigrades—allowed their preservation even at room temperature without losing their potential for supporting development after fertilization 1115 . These findings suggest that, although the entire mammalian body is susceptible to extreme environments, its cell nuclei can retain vital potential and that healthy offspring can be generated from them using recent reproductive biotechnology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most freeze-drying studies, the spermatozoa were snap-frozen without any attempt to maintain their membrane integrity (so called 'viability') [e.g. 80,98,99] while in other studies an attempt to obtain viable cells was made by using proper cryopreservation techniques [e.g. 90,100].…”
Section: Drying Spermatozoamentioning
confidence: 99%
“…These procedures include evaporating drying, vacuum of TEST‐yolk buffer, electrolyte‐free medium and sodium alginate extender (Bhowmick et al, ; Jaskey & Cohen, ; Kikuchi et al, ; Merino et al, ; Riel et al, ; Yániz et al, ). Recently, freeze‐dried mice spermatozoa under vacuum could fertilise a large number of oocytes and produce healthy offspring (Kamada et al, ).…”
Section: Introductionmentioning
confidence: 99%